Public image of the profession is associated with the choice of nursing career among Arab high school students: A cross‐sectional study. (14th September 2021) - Mohsen, Aseel; Bluvstein, Irit; Wilf Miron, Rachel; Kagan, Ilya
Abstract: Aims: The aim of this study is to examine (a) public image of nursing and the intention to choose nursing as a future career and (b) the relationship between the public image, gender roles and the choice of the nursing career among Arab high school students. Background: School graduates from the Arab sector represent an important social group with the potential to provide quality candidates for the nursing profession in Israel. Methods: In this cross‐sectional study, 138 high school students from two Arab schools in Israel completed a structured questionnaire. Results: One third of the sample intended to choose nursing as a future career. Students from families with a higher level of paternal education and those exposed to the work of nurses perceived nursing as more positive. The profession's public image contributed to the explanation of 21% of the variance of the intention to choose a nursing career. Conclusion: A positive public image of nursing contributes to decisions about choosing a nursing career in the future among Arab high school students. Implications for Nursing Management: School graduates may be influenced by providing information and presenting the role of a nurse as significant, as well as by emphasizing the positive image of nursing to parents and influential people in the Arab community.